Exploring the Influence of Artificial Intelligence on Financial Due Diligence Processes in Mergers and Acquisitions - Valtanen, Ella (2025)
Artificial intelligence (AI) is here to stay, and it is rapidly changing the world. AI refers to the ability of computers or systems to simulate human intelligence, such as learning, reasoning, and problem-solving, using algorithms and large data sets. As part of mergers and acquisitions, one or both parties conduct a due diligence review aimed at identifying the factors and risks that affect the purchase price. Organisations are increasingly relying on data-driven decisions, and AI technologies offer the potential to enhance the accuracy and efficiency of due diligence processes. At the beginning of the research, the current state of AI usage and its prevalence among those conducting financial due diligence (FDD) assignments is mapped out. The integration of AI into processes and systems also involves risks and challenges, which the re-search aims to explore. Additionally, the research seeks to identify potential areas that could be optimised or facilitated through the use of AI. The research focuses particularly on the Nordic countries. This master's thesis has been conducted as qualitative research. Its data consists of three separate thematic interviews and five reports produced by global consulting firms. The participants in the interviews were chosen through expert sampling. The data analysis was carried out inductively, meaning that the reasoning moves from practice to theory. AI is most used for text structuring, brainstorming, or proof-reading, areas in which it was also perceived to be beneficial. The research findings indicated that the significant barrier to increasing the use of AI is the immaturity of AI models. The responses provided by AI have not yet developed to the level required in financial due diligence reviews. According to the results, AI has not yet influenced decision-making or processes itself. Instead, AI was seen as having potential for data structuring and review, particularly in data rooms.